PERANCANGAN SISTEM INFORMASI NILAI SISWA DI SMP NEGERI 2 BERASIS WEB - F. Vipriani Manurung; Roni J Simamora; Rena Nainggolan (Universitas Methodist Indonesia, 2022)
Technology has advanced by leaps and bounds, as have human demands. Web technology system have become one of the most frequently used applications in the lives of ordinary mortals. By using a computer as a tool that is able to store and manage data quickly, precisely, and accurately. As a result, technological advances play an important and much needed role, especially in the field of Education or school. The problem in SMP Negeri 2 Kisaran is that administrative employees are still recording student grades into a collection of grades manually, so it takes a very long time. Therefore, the solution that can be done to solve these problems is to use the student value programming application that has been built. The results of research that has been done and the website that was built that can help and facilitate the task of administrative employees in managing student grades effectively and efficiently, as well as making reports on student grades as a result of student learning.